2014
DOI: 10.1007/s00167-014-3421-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the sagittal plane malpositioning of the patella and concomitant quadriceps hypotrophy on the patellofemoral joint: a finite element analysis

Abstract: Sagittal malalignment of the patellofemoral joint is a new concept that results in different loading patterns in the patellofemoral joint biomechanics. This malalignment in sagittal plane leads to increased loading values on the patellofemoral joint at 30° and 60° of the knee flexions. This new concept should be kept in mind during the course of diagnosis and treatment in patients with anterior knee pain. Definition of the exact biomechanical effects of the sagittal tilting will lead to the development of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…Sagittal patellar tilt leads to pathological loading by changing patellofemoral joint geometry as well as contact areas in cases of patellofemoral knee pain following tibial nailing [1]. To the best of our knowledge, the literature contains no study analysing the relationship between the chondromalacia patella and sagittal patellar tilt which might be a causative factor in patellar cartilage lesions by changing contact values and loading distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sagittal patellar tilt leads to pathological loading by changing patellofemoral joint geometry as well as contact areas in cases of patellofemoral knee pain following tibial nailing [1]. To the best of our knowledge, the literature contains no study analysing the relationship between the chondromalacia patella and sagittal patellar tilt which might be a causative factor in patellar cartilage lesions by changing contact values and loading distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The purposes of this study are: (1) to evaluate sagittal plane alignment in patients with chondromalacia patella via magnetic resonance imaging (MRI); (2) to analyse the relationship between the location of the patellar cartilaginous lesion and sagittal alignment; and (3) to investigate the relationship between the sagittal plane malalignment and patellofemoral loadings using finite element analysis. In the current study, it was hypothesized that the malalignment of the patella in the sagittal plane was related to chondromalacia patellae and this causes supraphysiological loadings on the patellofemoral joint.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods such as finite element (FE) analysis and joint-segment modeling are examples of musculoskeletal modeling that can estimate in vivo joint loading and mechanics [17,65,66]. Recent FE studies have been used to estimate measures such as bone strain [18] and have examined the effect of factors such as ligament reconstruction [67,68] and malpositioning of the patella [69,70]. These models allow for the simulation of six-degrees-of-freedom (three rotations and three translations) patella motion and are validated through comparison with cadaveric results.…”
Section: In Silicomentioning
confidence: 99%
“…cartilage damage and implant impingement) play an important role. [9][10][11][12][13] Thus, countersinkable biodegradable implants are on the rise to obtain anatomic reduction of articular fractures and to avoid secondary implant removal. Burkhart et al 14 found no significant differences in stability between headless compression screws (HCS) and lag screws in a biomechanical cadaver study with smaller cartilage defects produced by the HCS.…”
Section: Introductionmentioning
confidence: 99%